Efficient Perovskite Solar Cells Employing Inorganic Interlayers. Issue 3 (28th January 2016) - Xiao, Manda; Gao, Mei; Huang, Fuzhi; Pascoe, Alexander R.; Qin, Tianshi; Cheng, Yi‐Bing; Bach, Udo; Spiccia, Leone
Abstract: In this work, inverted structure CH3 NH3 PbI3 perovskite‐based solar cells (PSCs) employing different inorganic metal oxides as hole‐selective interlayers have been fabricated on ITO/NiO x, ITO/VO x and ITO/MoO x substrates and exhibit power conversion efficiencies (PCEs) of 10.6±0.6 %, 11.7±0.5 % and 5.9±0.5 %, respectively. The metal oxide layers deposited on ITO glass modify the substrate work function, leading to open circuit voltages above 1.0 V. Moreover, solar cells fabricated on ITO substrates without any metal oxide layer achieve a high PCE of 11.5 %, indicating that PSCs can perform well with a single selective contact. The inverted structure PSCs, with or without the metal oxide interlayers, show only a weak hysteresis in the J ‐ V measurements. Our work reveals that single selective contact PSCs with simplified device structures can be very efficient after optimization of each active layer, making them highly competitive with other types of thin film photovoltaic (PV) technologies. Abstract : Inverted‐structure perovskite solar cells employing different inorganic metal oxides as hole‐selective interlayers have been fabricated which exhibit little J ‐ V hysteresis and achieve power conversion efficiencies of over 10 %. The metal oxide layers deposited on ITO substrates were found to modify the work functions, leading to improvements in the V oc .